Crisis management in exchange rate policy - Joachim Starbatty (Intereconomics, 1986)
The behaviour of the dollar exchange rate last year and the concerted action by central banks in the autumn of 1985 have given renewed Impetus to the demand for internationally co-ordinated exchange rate management. How should such attempts at co-operation in the economic and monetary fields be viewed?
Keywords: 330; Monetary Policy